IDENTIFIKASI PENGETAHUAN IBU TENTANG IMUNISASI PCV DI PUSKESMAS TELUK TIRAM - Ruhmayanti, Nila; Nita Hestiyana; Dwi Sogi Sri Redjeki; Dede Mahdiyah (LPPM Universitas Sari Mulia, 2025)
Background: The highest number of pneumonia cases in South Kalimantan was in Banjarmasin City, numbering 2,408 or 21% of the total cases spread across 13 districts/cities. Pneumonia can cause death in babies so a mother must have good knowledge of this, namely by providing PCV immunization as a precaution. Based on a preliminary study conducted by researchers in April 2024 at the Teluk Tiram Community Health Center, of 6 mothers with babies, only 2 people knew about the benefits and objectives of PCV immunization, while the other 4 people did not know about the benefits and objectives of PCV immunization. Objective: Identifying mothers' knowledge about PCV immunization at Teluk Tiram Community Health Center. Methods : This research uses a descriptive method. The sample in the study was 45 mothers who brought immunized babies to the Teluk Tiram Community Health Center, Banjarmasin. Data analysis using univariate analysis techniques, namely by calculating the frequency of each question item in the categories of age, education, occupation and mother's level of knowledge. Results: Based on data analysis, it was found that the mother's age characteristics had the highest results, namely 35 respondents (78%) in the productive category, the highest results were maternal education characteristics, namely 31 respondents in the secondary education category (68%), the mother's employment characteristics had the highest results, namely the respondents Housewives were 29 respondents (64%), and of the 45 respondents, mothers' knowledge about PCV immunization was 35 respondents (78%) with good knowledge. Conclusion: 78% of mothers had good knowledge of PCV immunization Keywords: Pneumonia Cases, Maternal Knowledge, PCV